Blood absolute lymphocyte count and trajectory are important in understanding severe COVID-19 - Catharine I. Paules; Jacqueline A. Nordwall; Kathryn Shaw-Saliba; Judith A. Aberg; Edward M. Gardner; Anna L. Goodman; N. Kumarasamy; Shikha Vasudeva; David M. Vock; Crystal M. North; Jens Lundgren; Neil R. Aggarwal; et al. (BMC Infectious Diseases)
Abstract Background Low blood absolute lymphocyte count (ALC) may predict severe COVID-19 outcomes. Knowledge gaps remain regarding the relationship of ALC trajectory with clinical outcomes and factors associated with lymphopenia. Methods Our post hoc analysis of the Therapeutics for Inpatients with COVID-19 platform trial utilized proportional hazards models to assess relationships between Day (D) 0 lymphopenia (ALC < 0.9 cells/uL), D0 severe lymphopenia (ALC < 0.5 cells/uL) or lymphopenia trajectory between D0 and D5 with mortality and secondary infections, and with sustained recovery using Fine-Gray models. Logistic regression was used to assess relationships between clinical variables and D0 lymphopenia or lymphopenia trajectory. Results D0 lymphopenia (1426/2579) and severe lymphopenia (636/2579) were associated with increased mortality (aHR 1.48; 1.08, 2.05, p = 0.016 and aHR 1.60; 1.20, 2.14, p = 0.001) and decreased recovery (aRRR 0.90; 0.82, 0.99, p = 0.033 and aRRR 0.78; 0.70, 0.87, p < 0.001 respectively). Trial participants with persistent D5 lymphopenia had increased mortality, and increased secondary infections, and participants with persistent or new lymphopenia had impaired recovery, as compared to participants with no lymphopenia. Persistent and new lymphopenia were associated with older age, male sex; prior immunosuppression, heart failure, aspirin use, and normal body mass index; biomarkers of organ damage (renal and lung), and ineffective immune response (elevated IL-6 and viral nucleocapsid antigen levels). Similar results were observed with severe lymphopenia. Conclusions Lymphopenia was predictive of severe COVID-19 outcomes, particularly when persistent or new during hospitalization. A better understanding of the underlying risk factors for lymphopenia will help illuminate disease pathogenesis and guide management strategies.